A Prospective, Double-Blind, Randomized, Controlled Clinical Trial in the Gingivitis Prevention with an Oligomeric Proanthocyanidin Nutritional Supplement. (10th December 2017) - Díaz Sánchez, R. M.; Castillo-Dalí, G.; Fernández-Olavarría, A.; Mosquera-Pérez, R.; Delgado-Muñoz, J. M.; Gutiérrez-Pérez, J. L.; Torres-Lagares, D.
Abstract : Aim . To evaluate the effectiveness on tissue response of the new nutritional supplement made of oligomeric proanthocyanidins in induced gingivitis after 21 days of use. Material and Methods . A prospective, double-blind, randomized, controlled clinical trial was carried out on 20 patients; it is divided into an experimental group and a control group after fulfilling the selection criteria. Patients had to come 4 times during the study to register the Silness and Löe index, the gingival bleeding index, the plaque index, the inflammatory crevicular fluid study (IL6), and the changes in the brightness of the gingiva. No complementary hygiene methods were allowed during the 21 days. Results . The Silness and Löe index was higher in the control group than in the experimental group, reaching a twofold difference between the groups (p < 0.0001 ). The gingival bleeding index also supports this fact, since the bleeding was lower in the experimental group (p < 0.005 ). However, the dental plaque on the tooth surface according to the plaque index was 33% higher in the experimental group (p < 0.006 ). Some differences in the IL-6 were found in the crevicular fluid (p < 0.0001 ). Conclusion . Oligomeric proanthocyanidins have an effect on the periodontal tissue's health. No effects on the accumulation of plaque on the tooth surface were found, so further studies are needed to determine the nature of the plaque.